Sind Psychedelika schnell wirksame Antidepressiva?: Leitthema - Gründer, Gerhard; Brand, Manuela; Kärtner, Laura; Scharf, Dennis; Schmitz, Christian N.; Spangemacher, Moritz; Mertens, Lea Julia (Der Nervenarzt, 2022)
Background Psychedelics, such as psilocybin represent one of the most promising current therapeutic approaches in psychiatry. Objective Psychedelics seem to have not only potent antidepressant effects. Do they also work particularly quickly, i.e. within one day? Material and methods The available literature on clinical studies of psychedelics in depressive syndromes is presented both from the period up to the prohibition of these substances in the late 1960s as well as after the resumption of research in the 2000s. One focus is the speed of onset of antidepressant action. Results Only the clinical studies published since 2016 that meet modern methodological standards have also systematically examined the speed of the antidepressant onset of action. The published studies, which were almost exclusively carried out with psilocybin, so far show small sample sizes (the total number of patients with depression treated in published clinical studies is <200) and some of them have methodological weaknesses; however, they suggest a pronounced and very rapid onset of action within one day for depression, treatment-resistant depression and depression in the context of life-threatening cancer. Conclusion The available studies indicate a potent, rapid onset and in many cases long-lasting antidepressant effect over several months. The currently conducted studies with three-digit patient numbers will provide final information about the potential of psilocybin for depression.
Am Ende des Titels ist ein Fragezeichen geschrieben
Gesehen am 23.05.2025